Inferences About the Authentic Self- When Do Actions Say More Than Mental States? (article). - Johnson, Joel T.
Three studies involving 478 undergraduates examined the perceived importance of observable actions versus mental states in revealing the " true self" - the authentic and fundamental nature of a target person. results suggest that when people have only limited information about a target, they believe that an action is more diagnostic of the individuals' true self than the accompanying mental state. When participants have knowledge concerning chronic dispositional tendencies of the target, however, they judge that a chronic mental state is more diagnostic of the true self than a chronic action tendency. Considered together, the findings suggests that people conceptualize the true self as a relatively private entity but nevertheless believe that an action of a little-known person may be particularly informative about that individual. Perceived diagnosticity of the true self was partially mediated by inferences concerning the relative stability of actions versus states but not by inferences of volition. -- ( from the author).
Keywords: Psychology-Periodicals.